2022
DOI: 10.1155/2022/3147953
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Efficiency Measurement of Green Buildings and Its Spatial and Temporal Differences Based on a Three‐Stage Superefficient SBM‐DEA Model

Abstract: To explore the development of green building eco-efficiency in China, a three-stage superefficient SBM-DEA model was used to measure the green building eco-efficiency in China based on interprovincial panel data from 2013–2020, and the interprovincial and regional development patterns and evolutionary characteristics of green building eco-efficiency were analyzed from the time series and spatial dimensions. It is found that the overall level of green building efficiency in China is low, and there are significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Liu et al [33] presented a study of the eco-efficiency of buildings in China that went through a process of evolution, which showed that the growth gradient of efficient buildings gradually passed from an area of low-medium/medium efficiency to an area of medium/medium-high efficiency. For this reason, they recommended implementing green building policies, making the most of local comparative advantages, and coordinating and improving support policies for green buildings and related industries by generating tools for monitoring and optimizing the energy consumption of buildings.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [33] presented a study of the eco-efficiency of buildings in China that went through a process of evolution, which showed that the growth gradient of efficient buildings gradually passed from an area of low-medium/medium efficiency to an area of medium/medium-high efficiency. For this reason, they recommended implementing green building policies, making the most of local comparative advantages, and coordinating and improving support policies for green buildings and related industries by generating tools for monitoring and optimizing the energy consumption of buildings.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the scientificity, availability, comprehensiveness and representativeness of data [12,13,14,15], the following indicator system has been established by referring to the selection of indicators in relevant literature, as shown in Table 1. The input index selects the necessary manpower input, technology input and energy consumption for technological innovation, including the personnel equivalent, internal expenditure of funds and total energy consumption; The input indicators selected in this evaluation are the full-time equivalent of personnel, internal expenditure of funds and total energy consumption; The expected output indicators are the output of innovation achievements and the output of innovation economy, including the number of invention patents authorized and the sales revenue of new products.…”
Section: 3index Selectionmentioning
confidence: 99%
“…In recent years, remote sensing and spatial measurement software, such as the GEOGRAPHIC information system (Arcgis 10.2 ESRI (Environmental Systems Research Institute, Inc.) Redlands, CA, USA), have been widely used in regional evaluation. These technical tools can exert unique visual effects on plane base-maps by searching, storing, processing and analyzing geospatial data, and are closely integrated with geographic analysis tools, which has opened up a new way for people to analyze and address problems [37]. The introduction of these technologies can provide powerful scientific support for the evaluation of high-quality economic development and the formulation of management policies.…”
Section: Introductionmentioning
confidence: 99%